PERBANDINGAN MODEL GROUP INVESTIGATION DENGAN PROBLEM BASED LEARNING BERBASIS MULTIPLE INTELLIGENCE TERHADAP KEMAMPUAN MEMECAHKAN MASALAH SISWA SMA - Amalia Putri Wijayanti; Sumarmi Sumarmi; Ach. Amirudin (Graduate School of Universitas Negeri Malang, 2016)
The objectives of the study is comparing of Group Investigation model and Problem Based Learning model on Multiple Intelligences with Problem Solving capability. This study is quasi experiment with non equivalent group design. The subjects of this reaserch are the eleventh graders Social Science Senior High School of Batu 1. They are in the event semester of 2015/2016 academic year. They are categorized by their final grade of old and event semester. To evaluate Problem Solving capability of geography uses pretest and postest instrument that has been validated and reliable. It uses analysis of two way anava by SPSS 16.0 for Windows. The analysis shows that there is distinction Problem Solve of geography with group investigation model and problem based learning base on Multiple Intelligences. Learning using group investigation model based on Multiple Intelligences is more beneficial in case students outcome of geography then Problem Based Learning model base on Multiple Intelligences. It is proved by average value of Problem Solving capability Group Investigation model greater than Problem Based Learning model in which 4,2. While in case problem solving capability, Problem Based Learning model is greater 4 than Group Investigation model. Therefore, it can be concluded that Group Investigation model can be rising cognitive.Penelitian ini bertujuan untuk membandingkan model Group Investigation dengan Problem Based Learning berbasis Multiple Intelligences untuk mengukur kemampuan memecahkan masalah. Penelitian ini merupakan penelitian eksperimen semu dengan desain penelitian non equivalent group design. Subyek dalam penelitian ini siswa kelas XI IPS SMA Negeri 1 Kota Batu Semester Genap tahun ajaran 2015/2016. Penilaian Kemampuan memecahkan masalah menggunakan instrumen soal pretest dan posttest yang telah divalidasi dan uji reliabilitas. Analisis menggunakan two way anava dengan program SPSS 16.0 for Windows. Berdasarkan hasil analisis data diperoleh hasil penelitian terdapat perbedaan Kemampuan memecahkan masalah dengan menggunakan Group Investigation dan Problem Based Learning berbasis Multiple Intelligences. Rata-rata hasil belajar Group Investigation lebih tinggi 4,2 dibandingkan Problem Based Learning. Dapat disimpulkan bahwa penggunaan model Group Investigation berbasis Multiple Intelligences dapat mendorong siswa meningkatkan hasil belajar.